2007
DOI: 10.1103/physrevlett.99.146806
|View full text |Cite
|
Sign up to set email alerts
|

Topological Delocalization of Two-Dimensional Massless Dirac Fermions

Abstract: The beta function of a two-dimensional massless Dirac Hamiltonian subject to a random scalar potential, which, e.g., underlies theoretical descriptions of graphene, is computed numerically. Although it belongs to, from a symmetry standpoint, the two-dimensional symplectic class, the beta function monotonically increases with decreasing conductance. We also provide an argument based on the spectral flows under twisting boundary conditions, which shows that none of states of the massless Dirac Hamiltonian can be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
299
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(326 citation statements)
references
References 40 publications
23
299
4
Order By: Relevance
“…We have demonstrated that the algorithm provides an accuracy and efficiency comparable to the tight-binding model on a honeycomb lattice. In agreement with the existing literature 15,16,17,18 we have found that disorder that is smooth on the scale of the graphene lattice constant enhances conductivity at the Dirac point. The absence of intervalley scattering in the network model may prove useful for the study of these and other single-valley properties.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have demonstrated that the algorithm provides an accuracy and efficiency comparable to the tight-binding model on a honeycomb lattice. In agreement with the existing literature 15,16,17,18 we have found that disorder that is smooth on the scale of the graphene lattice constant enhances conductivity at the Dirac point. The absence of intervalley scattering in the network model may prove useful for the study of these and other single-valley properties.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results obtained in Refs. 15,16,17,18. The effect should not depend on the shape of the tiles in our model for the disorder.…”
Section: Correspondence Between Scattering Matrices Of Dirac Equamentioning
confidence: 91%
“…This means that in such samples there exists a minimal non-zero conductivity, which (together with symmetry and spectral flow arguments) led to the conclusion that there is no localization in 1D disordered graphene systems 13,40 . However, this statement (being correct in some sense) should be perceived with a certain caution.…”
Section: Transmission In Disordered Structuresmentioning
confidence: 99%
“…The effect of smooth disorder on transport in graphene has been recently analyzed theoretically by a number of authors, 15,23,24,25,26,27,28 finding once more striking differences with respect to the well known theory of disordered metals. 29 Due to the absence of inter-valley scattering and to chirality conservation, 20 this kind of disorder has the peculiarity of enhancing the conductivity with respect to the ballistic case, which is at odds with classical intuition.…”
Section: Introductionmentioning
confidence: 99%
“…23 suggests the existence of a universal minimal conductivity, whereas recent numerical simulations find that σ increases in a logarithmic fashion with the system size, 24 while the beta function exists (single parameter scaling) and always remains positive. 24,25 One must bear in mind, however, that the conclusions of Ref. 23 rely on a diffusive limit, so that direct comparison to the numerical calculations might not be straightforward.…”
Section: Introductionmentioning
confidence: 99%